Coexistence of two distinct Sulfurospirillum populations respiring tetrachloroethene—genomic and kinetic considerations. Issue 5 (6th March 2018) - Buttet, Géraldine Florence; Murray, Alexandra Marie; Goris, Tobias; Burion, Mélissa; Jin, Biao; Rolle, Massimo; Holliger, Christof; Maillard, Julien
Abstract: Two anaerobic bacterial consortia, each harboring a distinct Sulfurospirillum population, were derived from a 10 year old consortium, SL2, previously characterized for the stepwise dechlorination of tetrachloroethene (PCE) to cis -dichloroethene ( cis -DCE) via accumulation of trichloroethene (TCE). Population SL2-1 dechlorinated PCE to TCE exclusively, while SL2-2 produced cis -DCE from PCE without substantial TCE accumulation. The reasons explaining the long-term coexistence of the populations were investigated. Genome sequencing revealed a novel Sulfurospirillum species, designated ' Candidatus Sulfurospirillum diekertiae', whose genome differed significantly from other Sulfurospirillum spp. (78%–83% ANI). Genome-wise, SL2-1 and SL2-2 populations are almost identical, but differences in their tetrachloroethene reductive dehalogenase sequences explain the distinct dechlorination patterns. An extended series of batch cultures were performed at PCE concentrations of 2–200 μM. A model was developed to determine their dechlorination kinetic parameters. The affinity constant and maximal growth rate differ between the populations: the affinity is 6- to 8-fold higher and the growth rate 5-fold lower for SL2-1 than SL2-2. Mixed cultivation of the enriched populations at 6 and 30 μM PCE showed that a low PCE concentration could be the driving force for both functional diversity of reductive dehalogenases and niche specialization of organohalide-respiring bacteria with overlapping substrate ranges. Abstract : Long-term coexistence of closely related populations in a bacterial consortium respiring the groundwater pollutant tetrachloroethene relies on their significantly different kinetic parameters.